(untitled) (Ticontre. Teoria Testo Traduzione, 2021)
The article focuses on two collections edited by Ediesse, the publishing organ of the CGIL:Laboriosi oroscopi (2006) and Il lavoro e i giorni (2008). It analyzes the literary representation of socially "dominant" figures in professional relationships. Five figures were found and studied: the "weak master", told within a relationship based on care; the university "baron", whose symbolic power acts inside and outside the university; the "paternalistic master", inserted in the industrial context and who reproduces a model that only appears to be past; the "foolish master", considered as an idiot; the "archetypal master", an immaterial figure who, however, has an influence on the actions of subordinate characters.